Courage - Binns, Barbara (Harper, an imprint of HarperCollinsPublishers, 2018)
"Ever since T'Shawn's dad died, his mother has been struggling to keep the family afloat. So when he's offered a spot on a prestigious diving team at the local private swim club, he knows that joining would only add another bill to the pile. But T studies hard and never gets into trouble, so he thinks his mom might be willing to bear the cost ... until he finds out that his older brother, Lamont, is getting released early from prison. Luckily, T'Shawn is given a scholarship, and he can put all his frustration into diving practices. But when criminal activity increases in the neighborhood and people begin to suspect Lamont, T'Shawn begins to worry that maybe his brother hasn't left his criminal past behind after all. And he struggles to hold on to the hope that they can put the broken pieces of their damaged relationship back together."--Amazon.